KUALITAS SENSORIS DAGING AYAM KAMPUNG MERAWANG YANG DIBERI TEPUNG MAGGOT BSF SEBAGAI SUBSITUSI TEPUNG IKAN DALAM RANSUM) - Dhifa Hilmi; Dewi Wahyuni; Agung Puji Haryanto (Jurnal Peternakan Nusantara, 2025)
The purpose of this study is to test the effect of BSF Maggot flour as a substitute for fishmeal in rations on the sensory quality of Merawang native chicken meat. The treatment given is feeding with the following composition: R0: 0% maggot flour + 10% fish meal in ration; R1 : 2.5% maggot flour + 7.5% fishmeal in ration; R2: 5% maggot flour + 5% fishmeal in ration; R3 : 7.5% maggot flour + 2.5% fishmeal in ration; R4 ; 10% maggot flour + 0% fish meal in the ration; The parameters tested are hedonic test and hedonic quality test including, aroma, softness, color, taste, and juiceness. The results of Kruskal Wallis analysis of each treatment showed that feeding by replacing fishmeal with maggot flour gave a significant difference (P<0.05) in the hedonic test on aroma, color, softness and taste but did not differ significantly (P>0.05) on juiceness. The hedonic quality test showed significantly different results in aroma, taste, tenderness and color but no significant difference in meat juiceness. The conclusion of this study is that the substitution of fishmeal with maggot flour from the level of 2.5 to 10% can increase the panelists' preference for Merawang chicken meat and can improve the sensory quality, especially in the aroma, color, tenderness and taste of Merawang chicken meat.